The Horrifying Film Sedap Message Marks Awareness of Family Communication in the Toba Batak Community - Juli Purnawati; Iskandar Zulkarnain; Syafruddin Pohan (Persepsi: Communication Journal, 2023)
This film provides insight into the importance of effective communication in the family. This film also depicts the richness and complexity of Toba Batak culture. How these cultural symbols can be analyzed from a semiotic perspective. The formulation of this research problem is important to see how the horror film deliciously conveys the message of awareness of family communication in the Batak Toba community using semiotic analysis. Based on the conflict between a Batak family and their four children who migrated to the capital. The method used is a qualitative method with a cultural semiotic approach. The Toba Batak tribe adheres to very strict customs. This film is able to bring awareness to this through the conflicts and solutions presented in the story of this film. The results of the research are that language becomes messages and symbolic meanings that can be an inspiration for the public to increase awareness of communication within the family and help create a harmonious and happy family.